Two versus five stereotactic ablative radiotherapy treatments for localized prostate cancer: A quality of life analysis of two prospective clinical trials. (November 2019) - Alayed, Yasir; Quon, Harvey; Cheung, Patrick; Chu, William; Chung, Hans T.; Vesprini, Danny; Ong, Aldrich; Chowdhury, Amit; Panjwani, Dilip; Helou, Joelle; Pang, Geordi; Korol, Renee; et al.
Highlights: Two-fraction prostate SABR was very well tolerated with minimal late toxicity. There were significant signals of improved bowel and sexual QOL with 2 fractions. Early signals of efficacy (4yPSARR, PSA nadir and bDFS) are comparable. Abstract: Purpose: Stereotactic ablative radiotherapy (SABR) is appealing for prostate cancer (PCa) due to low α/β, and increasing the dose per fraction could improve the therapeutic index and lead to a better quality of life (QOL). Here we report the outcomes of a QOL comparison between two phase II clinical trials: two vs. five fraction prostate SABR. Methods: Patients had low or intermediate risk PCa. The doses prescribed were 26 Gy/2 and 40 Gy/5. Expanded prostate cancer index composite was collected. Urinary, bowel and sexual domains were analyzed. Minimal clinically important change (MCIC) was defined as >0.5 standard deviation. Results: 30 and 152 patients were treated with 2-fraction and 5-fraction SABR. Median follow-up was 55 and 62 months. Five-year biochemical failure rate was 3.3% and 4.6%. The 2-fraction cohort had a significantly better mean QOL over time in the bowel domain ( p  = 0.0004), without a significant difference in the urinary or sexual domains. The 2-fraction cohort had a significantly lower rate of bowel MCIC (17.8% vs 42.3%, p  = 0.01), but there was no difference in urinary (24.1% vs 35.7%) or sexual (15.3% vs 29.2%) MCIC. For MCIC x2 (moderate QOL change), the 2-fraction trial had significantly lower MCIC rates in both the bowel (7.1% vs 24%, p  = 0.04) and sexual (0 vs 17.6%, p  = 0.01) domains. Conclusions: 2-Fraction SABR is feasible to deliver and well tolerated, with significant signals of improved bowel and sexual QOL. A randomized trial of two vs. five fractions for prostate SABR is needed to confirm the promising findings of this study.